Boko Haram's terrorist campaign in Nigeria contexts, dimensions and emerging trajectories - Oriola, Temitope B.; Onuoha, Freedom Chukwudi; Oyewole, Samuel (Routledge studies in peace, conflict and security in Africa, 2022)
"This book investigates the devastating impacts of the Boko Haram terrorist campaign in Nigeria, reflecting on the group's historical context, organizational dynamics, and emerging trajectories"--